Studies on customer services optimisation by using the SCIM – an application of the agent base modelling (ABM) technology to service science. (19th January 2010) - Kamoshida, Akira; Terano, Takao; Jiang, Bin; Elias, Hasnat; , Takashi Kikuchi
This paper describes an application methodology of agent base modelling (ABM) technology for service science and a concept of the smart customer interaction modelling (SCIM) innovated from the ABM, which has created an optimised service design that is indispensable with regard to enhancing customer satisfaction, thus, enabling an improvement of customer service productivity and quality. The main concept of the SCIM is to maintain the corporate brand loyalty of customers. An actual adaptability of the SCIM for a car sales service is studied. Based on the results, we confirmed the SCIM technology had the capability to realise a maximised service quality. Some of the key issues found in the application case are also discussed.